The Effect of Virtual Reality on Learning Outcomes Mediated by Interaction and Learning Experiences (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In Indonesia, only a few educational institutions have implemented VR learning technology due to the lack of available content for learning and the insignificant effect for students after using VR. This study aims to examine the effect of VR learning technology (immersion, visualization, interaction) on learning outcomes (perceived learning effectiveness, satisfaction) with interaction experience (perceived usefulness, perceived ease of use) and learning experiences (motivation, interest, active learning) as mediators. 117 questionnaires are distributed to Junior High Schools, Senior High Schools, and Vocational High Schools students which have implemented the VR technology learningbased and implemented their classes with VR content, between the age of 12 until 19 years old. The data is analyzed by using Structural Equations Modelling (SEM) and Multiple Regression Analysis. We find VR learning technology affect student’s motivation and learning activity and also improve student learning outcomes in terms of perceived learning effectiveness dimension. On the other hand, the interaction experience was unperceived because of a lack of learning content characteristics for the immersive dimension that can affect the perceived usefulness and perceived ease of use. This research showed that the characteristics of VR learning technology affect student’s motivation and learning activeness. It improves student’s learning outcomes for perceived learning effectiveness.